Rear window [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Stewart, James, 1908-1997; Grace, Princess of Monaco, 1929-1982; Corey, Wendell, 1914-1968; Ritter, Thelma; Burr, Raymond, 1917-1993 (Alfred Hitchcock Collection., 2012)
A wheelchair bound photographer spies on his neighbors from his apartment window and becomes convinced one of them has committed murder.